2023
DOI: 10.1002/gj.4804
|View full text |Cite
|
Sign up to set email alerts
|

A timeline of the Cenozoic tectonic–magmatic–metamorphic evolution and development of ore resources in the Himalayas

Wei Zhang,
Song Qin,
Wen‐Lin Zhang
et al.

Abstract: A large concentration of ore deposits (i.e., tungsten, tin, lithium, beryllium, lead, zinc, silver, antimony and gold) related to metamorphism and hydrothermal activity of granite developed in the Himalayas and are located in the southern part of the Qinghai‐Tibet Plateau. As one of the newest and largest examples in the world of continental–continental collisional orogenic belts, the Himalayas are optimal for studying the coupling of continental collisions with metamorphic, tectonic, magmatic events and ore r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that as the degree of crystal differentiation of pegmatite increases, the major and trace elements and B isotopic compositions of tourmaline indicate certain changes [4,5]. According to the characteristics of trace elements in the Jiajika X03 vein Tur-IV tourmaline belt, the contents of Ti and Mn in tourmaline gradually increase from the core to the edge of a single pegmatite, while the content of V basically does not change [79][80][81]. Tur-I and Tur-II tourmaline show no evident ring development, and the chemical composition from the core to the edge has no apparent change.…”
Section: Metallogenic Significance Of Tourmaline From the Jiajika X03...mentioning
confidence: 96%
“…Previous studies have shown that as the degree of crystal differentiation of pegmatite increases, the major and trace elements and B isotopic compositions of tourmaline indicate certain changes [4,5]. According to the characteristics of trace elements in the Jiajika X03 vein Tur-IV tourmaline belt, the contents of Ti and Mn in tourmaline gradually increase from the core to the edge of a single pegmatite, while the content of V basically does not change [79][80][81]. Tur-I and Tur-II tourmaline show no evident ring development, and the chemical composition from the core to the edge has no apparent change.…”
Section: Metallogenic Significance Of Tourmaline From the Jiajika X03...mentioning
confidence: 96%
“…The formation of the Tethyan collisional orogenic belt experienced ocean‐continent subduction of the Tethyan oceanic plate and subsequent continent‐continent collision processes in different periods, accompanied by strong crust–mantle interactions and diversified economic mineralization (Cao et al, 2022; Deng et al, 2022). For example, along with the closure of the Cenozoic Neo‐Tethyan Ocean and collision of the Indian and Eurasian plates, many ore deposits were formed by the subduction of oceanic and continental crust under the Lhasa Plate in the north (Cao et al, 2019; Kong et al, 2023; Tang et al, 2021) and some rare metal deposits related to leucogranite were formed in the Himalayas in the south (Cao, Pei, Yu, Cao, et al, 2023; Zhang et al, 2023). Compared with the circum‐Pacific metallogenic domain and the Palaeo‐Asian Ocean metallogenic domain, the Tethyan metallogenic domain developed not only in the subduction stage but also in the main collisional and post‐collisional stages (Cao, Pei, Yu, Santosh, et al, 2023), showing the dominance of porphyry mineralization (Xu et al, 2022).…”
Section: Advances In Metallogeny and Tectonics Of The Eastern Tethyan...mentioning
confidence: 99%